1995
DOI: 10.1111/j.1464-410x.1995.tb07339.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the free Ca2+ in undiluted urine from stone formers and normal subjects using a new generation of ion‐selective electrodes

Abstract: Measurement of the Ca2+ in spot urine samples at a standard pH provides a more discriminative test than total Ca for the presence of urinary tract stones. The pH dependence of the Ca2+ may have important consequences in the formation of urinary tract stones. The poor correlation between measured and computed values of Ca2+ emphasizes the importance of accurate measurement of this variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…In position of samples from normal subjects and stone formers. a previous paper, we showed that the concentration of the ionized fraction of calcium in urine, [Ca2+], is a better discriminant of urine between stone formers and Materials and methods normal subjects [5]. Therefore, it is possible that factors altering the [Ca2+] in urine may enhance or diminish…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In position of samples from normal subjects and stone formers. a previous paper, we showed that the concentration of the ionized fraction of calcium in urine, [Ca2+], is a better discriminant of urine between stone formers and Materials and methods normal subjects [5]. Therefore, it is possible that factors altering the [Ca2+] in urine may enhance or diminish…”
Section: Introductionmentioning
confidence: 99%
“…Urine is although the total [Ca] remains constant [5]. However, the quantitative relationship between urinary pH and generally supersaturated with respect to calcium, oxalate and phosphate [1-3] so that their variation during the [Ca2+ ], and the pH-dependence of crystalline deposition in urine is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations